Comprehensive comparison on optical properties of samarium oxide (micro/nano) particles doped tellurite glass for optoelectronics applications - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2021)
Comprehensive comparison on optical properties of samarium oxide (micro/nano) particles doped tellurite glass for optoelectronics applications by Muhammad Noorazlan Abd Azis